Study of the animated feature film of The legend of La Llorona - Pomaquero-Yuquilema, Mayra; Furió-Vita, Dolores; López Izquierdo, María Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Since its beginnings, cinema has been strongly linked to literature through the adaptation of novels, the dissemination of literary heritage, the analysis of subjectivity, the theory of genres, the application of the categories of narratology to the study of filmic specifications, among many others. This study takes two literary stories and compares them through methodological and theoretical orientations of narratology with the animated version of The Legend of La Llorona, in order to determine similarities and differences. It also analyses certain elements of the cinematographic language that are consistent with the literary works in order to understand what makes them different and specific.